ANALISIS KEMAMPUAN PEMAHAMAN SISWA MENGGUNAKAN MODEL PEMBELAJARAN MURDER PADA MATERI KOORDINAT KARTESIUS KELAS VIII - Nisfa Destiana; Luvy Sylviana Zanthy; Asep Ikin Sugandi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
Classroom Action Research (CAR) aims to determine students' understanding of the Cartesian coordinates material for class VIII through the application of the MURDER model (Mood, Understand, Recall, Digest, Expand, Review). The subjects in the study were 18th graders at SMP Negeri 1 Cipeundeuy. The research was carried out in two cycles. The technique of collecting research data is by using observation techniques and giving description tests. The results of data collection were processed using qualitative data, these results were obtained from the results of students' pretest and posttest scores. These results can be said to be complete if they get a value of 75. From the results of research conducted by researchers, it showed an increase in the completeness of the description test after the pretest and posttest were carried out in each cycle. In the first cycle, which was carried out using the MURDER learning model, students' mastery increased from 16.67% to 61.6%. Cycle II with the MURDER learning model assisted by LKPD reached 83.3%.